Literature Study on Increasing Dribbling Agility Through Ball Feeling Training Methods and Ladder Drill Training - Mappaompo, M. Adam; Hasanuddin, M. Imran; Juhanis, Juhanis (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Football encompasses a range of fundamental strategies that hold significance in the game, such as passing, controlling, shooting, and dribbling. Dribbling is a technique that emphasises the cultivation of fluid and effective ball movement throughout a game, employing agility and speed to adeptly manoeuvre through changes in direction. The objective of this study was to assess the impact of ball-feeling training and ladder drill training on agility abilities in ball dribbling based on the provided background information. The literature review was conducted by searching for published journals using specific keywords relevant to the central study topic. Most literature studies indicate that practicing ball feeling and drill ladder training have a significant effect on agility, leading to an enhancement in an individual's ball dribbling skills. This to a comprehensive analysis of relevant literature, this research demonstrates the significant influence of ball-feeling training and ladder training on players' agility and dribbling ability.